Pendampingan dan Pelatihan Digital Marketing UMKM Toeng Kitchen melalui Instagram - Dwi Julian , Aditya; Ayumi , Hanafuki; Jodhy Iqbal Kusuma, Putra; Yuliawati, Evi (Madani : Indonesian Journal of Civil Society, 2025)
UMKM Toeng Kitchen is a small and medium enterprise engaged in traditional culinary located in Menganti District, Gresik Regency, East Java. UMKM Toeng Kitchen offers a variety of traditional snacks, ranging from wet cakes such as klepon, onde-onde, and layered cakes, to other sweet treats that pamper the tongue. With selected raw materials and a manufacturing process that maintains quality and taste, Toeng Kitchen MSME is committed to providing delicious, healthy, and safe products for customers. However, marketing constraints are a challenge for  UMKMToeng Kitchen. Amid the rapid development of technology, UMKM do not have tech-savvy workers. This situation makes UMKM Toeng Kitchen owners concerned about the growth and sustainability of their businesses. Therefore, this community service activity focuses on mentoring the creation of digital marketing and operational training for the Management Team. This activity has had a positive impact on UMKM Toeng Kitchen sales revenue. The results obtained from this activity include marketing effectiveness. By uploading product photos, videos, and reels that attract attention,  UMKM Toeng Kitchen can reach a wider customer base.